Mapping the Intellectual Core of Technology Adoption in Digital Startups: A Bibliometric Analysis via Bibliographic Coupling and Co‑Word Networks - Rosalin, Sovia; Raharjo, Kusdi; Utami, Hamidah Nayati; Prasetya, Arik (International Journal of Environment, Engineering and Education, 2025)
Digital startups are reshaping markets through the use of AI, cloud computing, and blockchain; however, scholarship on how these firms adopt technology remains fragmented. This study systematically maps the intellectual structure and thematic fronts of research on technology adoption in digital startups. A field-tagged Scopus search conducted in September 2025 (coverage 2000–2025) was cleaned and harmonized using a VOSviewer. After de-duplication, 2,243 documents were analyzed via bibliographic coupling (knowledge structure) and co-word analysis (thematic). Four coherent clusters emerge. Strategic innovation and leadership function as the governance backbone that shapes adoption decisions and risk appetite. Sustainable, data-driven business models translate adoption into performance outcomes through analytics capability and value capture. Corporate entrepreneurship within innovation ecosystems bridges firm-level capability with external partners, investors, and accelerators, linking adoption speed to ecosystem embeddedness. Digital business transformation operationalizes AI/cloud investments into processes and customer journeys. Cross-cutting co-word foci, such as perceived usefulness/user experience and organizational readiness, act as mechanisms connecting individual cognition with organizational capability. Emergent topics in policy, regulation, and platform governance appear as boundary conditions that enable or constrain adoption trajectories. The mapping provides an integrative lens organized along two axes: cognitive evaluation and organizational capability that jointly explain adoption in digital startups. It identifies gaps in external enablers and capability maturation paths. A forward-looking agenda is proposed, featuring multi-level models that link cognition, capability, and growth, as well as quasi-experimental evaluations of interface simplification and onboarding, cross-country comparisons of regulatory regimes, and longitudinal tracking of platform transitions.